2018
DOI: 10.1002/pmic.201700418
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Powdery Mildew–Infected, Susceptible, Resistant, and Immune Sunflower Genotypes

Abstract: Powdery mildew (PM, caused by Golovinomyces orontii) is one of the major diseases on sunflower that causes severe yield losses in the tropics. Sources of resistance to PM are reported in an exotic accession and some wild Helianthus species. The present study aims at quantitative proteomic analysis of susceptible, resistant, and immune genotypes of sunflower in response to PM infection at 3, 7, 10 days post infection. The majority of differentially expressed proteins in the resistant genotype belonged to oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 98 publications
(167 reference statements)
2
6
0
Order By: Relevance
“…Our findings are in line with a recent study which observed high up-regulation of HSF and heat shock proteins ( HSPs ) against biotrophic fungus [ 58 , 59 ]. HSF was also reported during bacterial infection which directly regulated Enhanced Disease Susceptibility 1 ( EDS1 ) and PR4 under SA-mediated signaling [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with a recent study which observed high up-regulation of HSF and heat shock proteins ( HSPs ) against biotrophic fungus [ 58 , 59 ]. HSF was also reported during bacterial infection which directly regulated Enhanced Disease Susceptibility 1 ( EDS1 ) and PR4 under SA-mediated signaling [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…HSP17.8 and WRKY simultaneously were regulated transcriptionally in the resistant potato genotypes where HSP chaperone activity kept the defense-related proteins active during abiotic stress. A recent report on powdery mildew infection in sunflowers, susceptible and resistant genotypes in relation to HSP70 demonstrated that HSP70 and other pathogenesis and defense-related proteins were more expressed and accumulated in the resistant genotypes than in the susceptible ones [101].…”
Section: Role Of Hsps In Plant Defensementioning
confidence: 99%
“…scolymus. Studies have been performed in H. annuus to investigate PM resistance and host-pathogen interactions [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%